Exploring the impact of google education tools on student engagement, learning motivation, and academic performance - Ting Tin Tin; Lionel Thum Zi Hua; Tiew Jia Jun; Thong Shao Bang; Wan Zhi Jie; Wan Nor Al-Ashekin Wan Husin; Ali Aitizaz; Lee Kuok Tiung; Ayodeji Olalekan Salau; Umar Farooq Khattak; Yasin Ahmed Siddiqui (Scopus, 2024)
Education tools are indeed important for both students and teachers to facilitate effective teaching and learning processes. However, some students and teachers are not familiar with the education tools, and some are unhappy with the educational tools when changing face-to-face to online learning. The most visible impact will be student engagement, learning motivation, and academic performance. This research aims to analyze the relationship between the level used in each Google Educational Tool daily and academic performance, along with the mediating variables of student engagement and learning motivation. 103 scholars from Tunku Abdul Rahman University Management and Technologies are invited to participate in this study. A correlation test and mediation analysis were conducted to measure the significance relationship between the variables using IBM SPSS 23.0 and Process Marco v4.2. The results showed the pattern that the Google Education Tool positively impacts student engagement and learning motivation. The results of the mediation analysis show that student engagement and learning motivation mediates the positive relationship between Google Shared Docs and academic performance. Furthermore, learning motivation as a mediator is also positively related to Google Drive and academic performance. However, some mediators do not show a significant relationship between dependent and independent variables. This research is important in increasing the initiative of the student involved in the use of Google Education Tool and in achieving a higher level of engagement and learning motivation to achieve better academic performance.